Unsaturated resin composition for artificial stone and preparation method thereof

By adding modification additives and maleic anhydride to the unsaturated resin-based material, the problems of yellowing appearance, aging and mechanical properties of unsaturated polyester resin in artificial stones are solved, and the effects of improving its flame retardancy, water resistance and extending service life are achieved.

CN119528481AActive Publication Date: 2025-02-28GUANGDONG MEIHENG NEW MATERIAL TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411691340.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Unsaturated polyester resins have problems in artificial stones such as yellow appearance, aging performance and degradation of mechanical properties, which affect their service life and performance.

Method used

The appearance and performance are improved by adding modification additives and maleic anhydride to the unsaturated resin-based material. Modification additives enhance the flame retardancy and UV resistance of the resin by grafting the modified lignin and octadecyl trichlorosilane on the surface of nanotitanium dioxide.

Benefits of technology

It effectively extends the service life of artificial stone, improves its flame retardant properties and water resistance, and inhibits the aging and yellowing of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151034450000081
    Figure BDA0005151034450000081
  • Figure BDA0005151034450000091
    Figure BDA0005151034450000091
  • Figure BDA0005151034450000101
    Figure BDA0005151034450000101
Patent Text Reader

Abstract

The invention relates to the field of unsaturated resin compositions, and discloses an unsaturated resin composition for artificial stone and a preparation method thereof, the unsaturated resin composition comprises unsaturated resin, a modified additive, maleic anhydride and a curing agent; the unsaturated resin comprises unsaturated polyester and a polymerizable monomer, the unsaturated polyester is a polymerization product of polyacid and polyol, and the polymerizable monomer comprises a styrene monomer; the modified additive is prepared by grafting modified lignin and octadecyl trichlorosilane on the surface of nano titanium dioxide, and the modified lignin is prepared by carrying out grafting reaction on oxidized lignin, p-phenylenediamine and DOPO (9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and then further grafting with terephthalaldehyde, gamma-aminopropyltriethoxysilane and DOPO. The modified additive and maleic anhydride are added into the unsaturated resin-based material, so that the problems of appearance yellowing, water resistance and flame retardance of the material are solved, the defects of performance aging, mechanical property reduction and the like of the material are inhibited, and the service life of the artificial stone is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of unsaturated resin compositions, and in particular relates to an unsaturated resin composition for artificial stone and a preparation method thereof. Background Art

[0002] Artificial stone is a practical building material that uses polymers. Its manufacturing process is a chemical material reaction process. It is a new type of environmentally friendly composite material that has been produced and continuously improved with the progress of social science and technology. It is mainly used in the building decoration industry. Compared with traditional building materials such as stainless steel and ceramics, artificial stone not only has diverse functions and rich colors, but also has a wider range of applications. Artificial stone is made by mixing unsaturated polyester resin with fillers and pigments through a certain processing procedure. Artificial stone has the advantages of being non-toxic, easy to cut, and can be arbitrarily mixed in color and cast in any shape.

[0003] Unsaturated polyester resin is a linear polymer compound formed by the condensation of diols and unsaturated dicarboxylic acids (anhydrides). It has the characteristics of low price, simple production process, high transparency, etc. Its application in the field of life is becoming more and more extensive. However, the waterproofness and heat resistance of unsaturated polyester resin are not outstanding. Improving its toughness and flame retardancy is also a current research focus. In addition, since unsaturated polyester resin is a linear polymer compound containing ester bonds, it generally contains a large number of benzene rings. Long-term exposure to ultraviolet rays will cause the aromatic structure therein to be transformed into a dark quinone structure, resulting in yellowing and aging of the product, affecting the appearance and life. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide an unsaturated resin composition for artificial stone and a preparation method thereof, add a modifying additive and maleic anhydride to the unsaturated resin-based material, improve the yellowing of the appearance and water resistance and flame retardancy of the unsaturated resin-based material, inhibit the aging of the performance and the decline of the mechanical properties of the unsaturated resin-based material, and effectively extend the service life of the artificial stone.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight: 50-70 parts of unsaturated resin, 10-20 parts of modifying additive, 5-15 parts of maleic anhydride and 2-5 parts of curing agent; the unsaturated resin comprises unsaturated polyester and polymerizable monomer, the unsaturated polyester is a polymerization product of polyacid and polyol, and the polymerizable monomer comprises styrene monomer; the modifying additive is obtained by grafting modified lignin and octadecyltrichlorosilane on the surface of nano titanium dioxide by chemical reaction, wherein the modified lignin is obtained by grafting oxidized lignin with p-phenylenediamine and DOPO by chemical reaction, and then further grafting with terephthalaldehyde, γ-aminopropyltriethoxysilane and DOPO.

[0007] Preferably, the curing agent is tert-butyl peroxy-2-ethylhexanoate.

[0008] Preferably, the preparation method of the unsaturated resin comprises the following steps: taking phthalic acid, maleic anhydride and propylene glycol in a reactor, heating to 95-105°C, stirring and performing polycondensation reaction after the raw materials are dissolved, initially heating to 155-170°C and maintaining the constant temperature for 20-30 minutes, heating again to 205-210°C and reacting at the constant temperature for 2-3 hours, then diluting and cooling, adding the inhibitor hydroquinone when the temperature drops to 175-185°C, adding styrene when the temperature drops to 120-125°C with continuous stirring, and then rapidly stirring until the temperature drops to 55-65°C to prepare the unsaturated resin.

[0009] Preferably, the molar ratio of phthalic acid, maleic anhydride and propylene glycol is 1-1.5:1-1.5:2-3.

[0010] Preferably, the heating rate of the initial heating is 8-10° C. / h, and the heating rate of the second heating is 10-12° C. / h.

[0011] Preferably, the preparation method of the modified additive comprises the following steps:

[0012] A. Put kraft lignin in a reactor, add sodium hydroxide solvent, hydrogen peroxide hydrogenation agent and molybdenum trioxide catalyst, react at 65-75°C for 3-5h, then adjust the pH value of the system to 2-3 with dilute hydrochloric acid, continue to react at 75-85°C for 20-30min, and after the reaction is completed, filter, wash and dry to prepare oxidized lignin;

[0013] B. Put oxidized lignin, p-phenylenediamine and DOPO in a reactor, add ethanol solvent, and react at 70-85°C for 5-15 minutes. After the reaction is completed, filter, wash and dry to prepare functionalized lignin.

[0014] C. Take the functionalized lignin, terephthalaldehyde and γ-aminopropyltriethoxysilane in a reactor, add ethanol solvent, place it under reflux reaction at 55-70°C for 4-6 hours, take DOPO dissolved in ethanol and add it to the reactor, place it under 70-85°C for further reaction for 5-7 hours, and after the reaction is completed, filter, wash and dry to prepare modified lignin;

[0015] D. Take nano titanium dioxide and add anhydrous ethanol for ultrasonic dispersion to obtain a suspension, take modified lignin and deionized water and mix them evenly, place them at 65-75°C for stirring and reacting for 0.5-1h to obtain a hydrolyzate, put the suspension, hydrolyzate and octadecyltrichlorosilane into a reactor, use dilute hydrochloric acid to adjust the pH value of the system to 4-5, then place them at 65-75°C for continuous stirring and reacting for 2-4h, and after the reaction is completed, filter, wash and dry to prepare a modified additive.

[0016] Preferably, in step B, the mass ratio of oxidized lignin, p-phenylenediamine and DOPO is 1-1.4:1:2-2.5.

[0017] Preferably, in step C, the mass ratio of the functionalized lignin, terephthalaldehyde, γ-aminopropyltriethoxysilane and DOPO is 2-3:1.3-2:1.2-1.7:3-3.5.

[0018] Preferably, in step D, the mass ratio of nano-titanium dioxide, modified lignin and octadecyltrichlorosilane is 3-5:2-5:4-6.

[0019] The method for preparing the unsaturated resin composition for artificial stone as described above comprises the following steps: taking parts by weight of an unsaturated resin, a modifying additive and maleic anhydride, heating them at 65-80° C. to melt the maleic anhydride, and then stirring them until they are cooled to room temperature, adding parts by weight of a curing agent thereto, stirring them evenly, pouring them into a mold, curing them at 55-65° C. for 0.5-1 h, and then heating them to 80-85° C. to continue curing them for 1-1.5 h, so as to prepare the unsaturated resin composition for artificial stone.

[0020] Beneficial effects of the present invention:

[0021] The invention uses kraft lignin as a raw material, increases the content of carbonyl groups in lignin through an oxidation reaction, and reacts the carbonyl group in the oxidized lignin structure with the amino group at one end of p-phenylenediamine and the PH bond in the DOPO structure to prepare nitrogen-phosphorus modified functionalized lignin, thereby grafting the antioxidant p-phenylenediamine and the flame retardant DOPO onto the surface of the lignin, inhibiting the aging decomposition and yellowing of unsaturated resin-based materials, and giving the unsaturated resin-based materials good flame retardant properties, and then reacting the functionalized lignin, terephthalaldehyde and γ-aminopropyltriethoxysilane, so that the aldehyde groups at both ends of the terephthalaldehyde react with the amino group in the functionalized lignin structure and the amino group in the γ-aminopropyltriethoxysilane structure to generate two CH=N groups, and further grafting DOPO to undergo an addition reaction to prepare The modified lignin is beneficial to the dispersion of lignin in the unsaturated resin-based material, and the mechanical properties and flame retardant properties of the matrix are further improved. At the same time, the present invention condenses the silicon hydroxyl groups in the modified lignin and the octadecyl trichlorosilane structure with the hydroxyl groups on the surface of nano titanium dioxide to prepare a modified additive, wherein the nano titanium dioxide is used as an inorganic ultraviolet shielding agent, and has good weather resistance and heat resistance. Moreover, due to its special photocatalytic activity, it has a strong antibacterial and sterilization ability after absorbing ultraviolet light energy, and octadecyl trichlorosilane is used as a long hydrophobic chain structure. The modified lignin and octadecyl trichlorosilane are grafted to the surface of nano titanium dioxide, which is beneficial to the dispersion of nano titanium dioxide, so that its mechanical properties and ultraviolet light aging resistance are fully exerted, and at the same time, the unsaturated resin-based material is given excellent waterproof and stain-resistant properties. The present invention adds a modified additive to the unsaturated resin-based material, improves the yellowing and water-resistant flame retardant problems of the unsaturated resin-based material, inhibits the defects of performance aging and mechanical property degradation of the unsaturated resin-based material, and effectively prolongs the service life of the artificial stone. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1 A method for preparing an unsaturated resin comprises the following steps:

[0024] Phthalic acid, maleic anhydride and propylene glycol were measured in a molar ratio of 1:1:2.15 in a reactor, and the temperature was raised to 100°C. After the raw materials were dissolved, stirring was started for polycondensation reaction. The temperature was initially raised to 160°C and kept constant for 30 minutes at a heating rate of 10°C / h. The temperature was raised to 210°C again and kept constant for 3 hours at a heating rate of 12°C / h. The temperature was then diluted and cooled. When the temperature dropped to 180°C, 18 mg of inhibitor hydroquinone was added. After continuous stirring and cooling to 120°C, 60 mL of styrene was added, and then rapid stirring was performed until the temperature dropped to 60°C to prepare an unsaturated resin.

[0025] Embodiment 2 A method for preparing a modified additive comprises the following steps:

[0026] A. Take 3.2g of kraft lignin in a reactor, add 10mL of 2.5wt% sodium hydroxide solvent, 15mL of hydrogen peroxide oxidizing agent and 0.15g of molybdenum trioxide catalyst, place it at 70°C for 4h, then adjust the pH value of the system to 2 with dilute hydrochloric acid, continue to place it at 80°C for 30min, and after the reaction is completed, filter, wash and dry to prepare oxidized lignin;

[0027] B. Take 2.5g of oxidized lignin, 2g of p-phenylenediamine and 4.5g of DOPO in a reactor, add 50mL of ethanol solvent, and react at 75°C for 10min. After the reaction is completed, filter, wash and dry to prepare functionalized lignin;

[0028] C. Take 3g of functionalized lignin, 1.6g of terephthalaldehyde and 1.5g of γ-aminopropyltriethoxysilane in a reactor, add 50mL of ethanol solvent, place under reflux reaction at 60°C for 5h, take 3g of DOPO dissolved in 20mL of ethanol and add to the reactor, place under 80°C for further reaction for 6h, and after the reaction is completed, filter, wash and dry to prepare modified lignin;

[0029] D. Take 3g of nano titanium dioxide and add it to 100mL of anhydrous ethanol for ultrasonic dispersion to obtain a suspension. Take 2g of modified lignin and 30mL of deionized water and mix them evenly. Place it at 70°C for stirring and reacting for 1h to obtain a hydrolyzate. Put the suspension, hydrolyzate and 4.8g of octadecyltrichlorosilane into a reactor, adjust the pH value of the system to 4 with dilute hydrochloric acid, and then place it at 70°C for continuous stirring and reacting for 4h. After the reaction is completed, filter, wash and dry to prepare a modified additive.

[0030] Embodiment 3 An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight:

[0031] 55 parts of the unsaturated resin prepared in Example 1, 12 parts of the modified additive prepared in Example 2, 7 parts of maleic anhydride, and 2 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0032] The preparation method of the unsaturated resin composition for artificial stone comprises the following steps:

[0033] Take parts by weight of an unsaturated resin, a modifying additive and maleic anhydride and heat them at 70°C to melt the maleic anhydride, then stir until cooled to room temperature, add parts by weight of a curing agent, stir evenly, pour into a mold, place at 60°C for curing for 0.5h, then heat to 85°C and continue curing for 1h to prepare an unsaturated resin composition for artificial stone.

[0034] Embodiment 4 An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight:

[0035] 62 parts of the unsaturated resin prepared in Example 1, 15 parts of the modified additive prepared in Example 2, 10 parts of maleic anhydride, and 4 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0036] The preparation method of the unsaturated resin composition for artificial stone is the same as that in Example 3.

[0037] Embodiment 5 An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight:

[0038] 70 parts of the unsaturated resin prepared in Example 1, 18 parts of the modified additive prepared in Example 2, 14 parts of maleic anhydride, and 5 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0039] The preparation method of the unsaturated resin composition for artificial stone is the same as that in Example 3.

[0040] Comparative Example 1 A method for preparing a modified additive comprises the following steps:

[0041] A. Take 3.2g of kraft lignin in a reactor, add 10mL of 2.5wt% sodium hydroxide solvent, 15mL of hydrogen peroxide oxidizing agent and 0.15g of molybdenum trioxide catalyst, place it at 70°C for 4h, then adjust the pH value of the system to 2 with dilute hydrochloric acid, continue to place it at 80°C for 30min, and after the reaction is completed, filter, wash and dry to prepare oxidized lignin;

[0042] B. Take 2.5g of oxidized lignin, 2g of p-phenylenediamine and 4.5g of DOPO in a reactor, add 50mL of ethanol solvent, and react at 75°C for 10min. After the reaction is completed, filter, wash and dry to prepare a modified additive.

[0043] Comparative Example 2 A method for preparing a modified additive comprises the following steps:

[0044] A. Take 3.2g of kraft lignin in a reactor, add 10mL of 2.5wt% sodium hydroxide solvent, 15mL of hydrogen peroxide oxidizing agent and 0.15g of molybdenum trioxide catalyst, place it at 70°C for 4h, then adjust the pH value of the system to 2 with dilute hydrochloric acid, continue to place it at 80°C for 30min, and after the reaction is completed, filter, wash and dry to prepare oxidized lignin;

[0045] B. Take 2.5g of oxidized lignin, 2g of p-phenylenediamine and 4.5g of DOPO in a reactor, add 50mL of ethanol solvent, and react at 75°C for 10min. After the reaction is completed, filter, wash and dry to prepare functionalized lignin;

[0046] C. Take 3g of functionalized lignin, 1.6g of terephthalaldehyde and 1.5g of γ-aminopropyltriethoxysilane in a reactor, add 50mL of ethanol solvent, and reflux at 60°C for 5h. Take 3g of DOPO, dissolve it in 20mL of ethanol and add it to the reactor, and continue to react at 80°C for 6h. After the reaction is completed, filter, wash and dry to prepare the modified additive.

[0047] Comparative Example 3 An unsaturated resin composition for artificial stone, comprising the following raw materials in parts by weight:

[0048] 70 parts of the unsaturated resin prepared in Example 1, 18 parts of the modified additive prepared in Comparative Example 1, 14 parts of maleic anhydride, and 5 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0049] The preparation method of the unsaturated resin composition for artificial stone is the same as that in Example 3.

[0050] Comparative Example 4 An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight:

[0051] 70 parts of the unsaturated resin prepared in Example 1, 9 parts of the modified additive prepared in Comparative Example 2, 9 parts of nano titanium dioxide, 14 parts of maleic anhydride, and 5 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0052] The preparation method of the unsaturated resin composition for artificial stone is the same as that in Example 3.

[0053] Comparative Example 5 An unsaturated resin composition for artificial stone comprises the following raw materials in parts by weight:

[0054] 70 parts of the unsaturated resin prepared in Example 1, 9 parts of lignin, 9 parts of nano titanium dioxide, 14 parts of maleic anhydride, and 5 parts of curing agent tert-butyl peroxy-2-ethylhexanoate.

[0055] The preparation method of the unsaturated resin composition for artificial stone is the same as that in Example 3.

[0056] Performance Testing

[0057] The unsaturated resin compositions prepared in Examples 3-5 and Comparative Examples 3-5 were subjected to performance testing:

[0058] (1) Mechanical properties and flame retardant properties test: The tensile strength was tested by preparing dumbbell-shaped tensile specimens according to GB / T 1040.2, and the tensile rate was 50 mm / min. The impact strength was tested by preparing rectangular specimens according to GB / T 1843-2008, and a cantilever pendulum impact tester was used for testing. The bending performance was tested by preparing rectangular specimens according to GB / T 9341-2008, and a universal testing machine was used for testing, and the test speed was 30 mm / min. The flame retardant properties of the samples were tested according to the limiting oxygen index, and the data results are shown in Table 1.

[0059] Table 1 Test results of mechanical properties and flame retardant properties of samples

[0060]

[0061] It can be seen from the data in Table 1 that the unsaturated resin composition prepared in Examples 3-5 of the present invention has high tensile strength, flexural strength, impact strength and limiting oxygen index, and has good mechanical properties and flame retardancy. Among them, the modified additive component in Comparative Example 3 only grafts oxidized lignin with p-phenylenediamine and DOPO, and its measured mechanical properties and flame retardancy are worse than those of Examples 3-5, because DOPO and nano-titanium dioxide are not further grafted. In Comparative Example 4, the modified additive component is simply mixed with nano-titanium dioxide, and its measured tensile strength, flexural strength and impact strength are lower than those of Examples 3-5. The reason may be that the agglomeration phenomenon of nano-titanium dioxide causes its mechanical properties to decrease. In Comparative Example 5, lignin and nano-titanium dioxide are simply mixed. Since the flame retardant component is not grafted, and lignin and nano-titanium dioxide are unevenly dispersed in the matrix, its measured mechanical properties and flame retardancy are significantly lower than those of Examples 3-5.

[0062] (2) Thermal oxygen aging resistance test: Referring to GB / T 7141-2008, an accelerated thermal oxygen aging test was carried out in a constant temperature blast drying oven at 150°C. The samples were taken out at different time periods and tested after cooling. The yellowness index was calculated using a fully automatic colorimeter according to HG / T 3862-2006. The data results are shown in Table 2.

[0063] (3) Test of UV aging resistance: The samples were placed in a UV aging test chamber and four 40W UV340 type UV lamps were used. The samples were taken out at intervals for testing. The yellowness index was calculated using a fully automatic colorimeter according to HG / T 3862-2006. The data results are shown in Table 2.

[0064] (4) Water absorption test: Take an unsaturated resin composition and add distilled water. Experiments are carried out in a constant temperature water bath at 20°C, 60°C and 100°C. The water before immersion in water is recorded as M1, and the water after immersion in water is recorded as M2. After the completion of immersion for 12 hours, the water absorption K is calculated, K = [(M2-M1) / M1] × 100%. The smaller K is, the more water-resistant the resin is, and the larger K is, the stronger the water absorption capacity is. The data results are shown in Table 2.

[0065] Table 2 Test results of yellowing resistance and waterproof performance of samples

[0066]

[0067]

[0068] As can be seen from the data in Table 2, the unsaturated resin composition prepared in Examples 3-5 of the present invention has better yellowing resistance and water resistance than Comparative Examples 3-5. Among them, the UV aging yellow index and water absorption rate measured in Comparative Example 3-4 are higher than those in Example 3-5, because the modified additive component does not introduce nano titanium dioxide or is simply mixed with nano titanium dioxide, and no hydrophobic long chain is introduced, resulting in its UV yellowing resistance and water resistance being lower than those in Example 3-5. The thermal oxygen aging yellow index, UV aging yellow index and water absorption rate measured in Comparative Example 5 are higher than those in Example 3-5, because lignin and nano titanium dioxide are simply mixed, and the antioxidant p-phenylenediamine and hydrophobic long chain are not grafted, resulting in its yellowing resistance and water resistance being lower.

[0069] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0070] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An unsaturated resin composition for artificial stone, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of unsaturated resin, 10-20 parts of modifying additive, 5-15 parts of maleic anhydride and 2-5 parts of curing agent; the unsaturated resin comprises unsaturated polyester and polymerizable monomer, the unsaturated polyester is a polymerization product of polyacid and polyol, and the polymerizable monomer comprises styrene monomer; the modifying additive is obtained by grafting modified lignin and octadecyltrichlorosilane on the surface of nano titanium dioxide by chemical reaction, wherein the modified lignin is obtained by grafting oxidized lignin with p-phenylenediamine and DOPO by chemical reaction, and then further grafting with terephthalaldehyde, γ-aminopropyltriethoxysilane and DOPO.

2. The unsaturated resin composition for artificial stone according to claim 1, characterized in that: The curing agent is tert-butyl peroxy-2-ethylhexanoate.

3. The unsaturated resin composition for artificial stone according to claim 1, characterized in that: The preparation method of the unsaturated resin comprises the following steps: taking phthalic acid, maleic anhydride and propylene glycol in a reactor, heating to 95-105° C., stirring to carry out polycondensation reaction after the raw materials are dissolved, initially heating to 155-170° C. and keeping the temperature constant for 20-30 minutes, heating again to 205-210° C. and keeping the temperature constant for 2-3 hours, then diluting and cooling, adding a polymerization inhibitor hydroquinone when the temperature drops to 175-185° C., adding styrene when the temperature drops to 120-125° C. by continuous stirring, and then rapidly stirring until the temperature drops to 55-65° C. to prepare the unsaturated resin.

4. The unsaturated resin composition for artificial stone according to claim 3, characterized in that: The molar ratio of the phthalic acid, maleic anhydride and propylene glycol is 1-1.5:1-1.5:2-3.

5. The unsaturated resin composition for artificial stone according to claim 3, characterized in that: The heating rate of the initial heating is 8-10°C / h, and the heating rate of the second heating is 10-12°C / h.

6. The unsaturated resin composition for artificial stone according to claim 1, characterized in that: The preparation method of the modified additive comprises the following steps: A. Put kraft lignin in a reactor, add sodium hydroxide solvent, hydrogen peroxide hydrogenation agent and molybdenum trioxide catalyst, react at 65-75°C for 3-5h, then adjust the pH value of the system to 2-3 with dilute hydrochloric acid, continue to react at 75-85°C for 20-30min, and after the reaction is completed, filter, wash and dry to prepare oxidized lignin; B. Put oxidized lignin, p-phenylenediamine and DOPO in a reactor, add ethanol solvent, and react at 70-85°C for 5-15 minutes. After the reaction is completed, filter, wash and dry to prepare functionalized lignin. C. Take the functionalized lignin, terephthalaldehyde and γ-aminopropyltriethoxysilane in a reactor, add ethanol solvent, place it under reflux reaction at 55-70°C for 4-6 hours, take DOPO dissolved in ethanol and add it to the reactor, place it under 70-85°C for further reaction for 5-7 hours, and after the reaction is completed, filter, wash and dry to prepare modified lignin; D. Take nano titanium dioxide and add anhydrous ethanol for ultrasonic dispersion to obtain a suspension, take modified lignin and deionized water and mix them evenly, place them at 65-75°C for stirring and reacting for 0.5-1h to obtain a hydrolyzate, put the suspension, hydrolyzate and octadecyltrichlorosilane into a reactor, use dilute hydrochloric acid to adjust the pH value of the system to 4-5, then place them at 65-75°C for continuous stirring and reacting for 2-4h, and after the reaction is completed, filter, wash and dry to prepare a modified additive.

7. The unsaturated resin composition for artificial stone according to claim 6, characterized in that: In the step B, the mass ratio of oxidized lignin, p-phenylenediamine and DOPO is 1-1.4:1:2-2.

5.

8. The unsaturated resin composition for artificial stone according to claim 6, characterized in that: In the step C, the mass ratio of the functionalized lignin, terephthalaldehyde, γ-aminopropyltriethoxysilane and DOPO is 2-3:1.3-2:1.2-1.7:3-3.

5.

9. The unsaturated resin composition for artificial stone according to claim 6, characterized in that: In the step D, the mass ratio of nano titanium dioxide, modified lignin and octadecyltrichlorosilane is 3-5:2-5:4-6.

10. A method for preparing an unsaturated resin composition for artificial stone according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: taking parts by weight of an unsaturated resin, a modification additive and maleic anhydride, heating them at 65-80°C to melt the maleic anhydride, stirring them until they are cooled to room temperature, adding parts by weight of a curing agent thereto, stirring them evenly, pouring them into a mold, curing them at 55-65°C for 0.5-1h, then heating them to 80-85°C and continuing curing them for 1-1.5h to prepare an unsaturated resin composition for artificial stone.

Citation Information

Patent Citations

  • Modified unsaturated polyester resin and preparation method thereof

    CN108084419A

  • Nano titanium dioxide powder dispersion liquid and preparation method thereof

    CN116082861A

  • Nano titania modified unsaturated polyester resin and its prepn.

    CN1389492A

  • Process for preparing modified lignocellulose sulfonate graft copolymer

    CN1693342A

  • Composition de resine de revetement et procede pour sa production

    FR2723376A1